ANALISIS PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR KECAMATAN TANJUNGKARANG PUSAT - Andy Mulyadinata (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2014)
Performance appraisal (performance appraisal) is the process in which organizationsevaluating or assessing the performance of the employee. This activity can repair human resourcedecisions and provide feedback to employees about their work. Besides the factor of leadershipskills, motivational factor also affect employees work productivity.The results of the calculation of the correlation of each variable showed that leadership styleand motivation were positively correlated with Work Productivity For the calculation of the regressionequation derived an equation Y = 2.129 + 0.218 X1 + 0.683 X2. T test results showed that thecoefficient of X1 (Leadership Style has no effect on labor productivity, while X (Motivation)significantly affect work productivity. Results of F test showed that the Leadership Style andMotivation give significant effect on Work Productivity.